High-entropy perovskite oxide material and preparation method and application thereof
Through the acrylamide monomer copolymerization system and water bath heating method, the preparation process of high-entropy perovskite oxide materials is simplified, and the problems of low preparation efficiency and complex process in the prior art are solved, and small particle size, high purity and catalyticity are obtained. A material that is highly active, suitable for SOFC and hydrogen and oxygen sensors.
Patent Information
- Application Number
- CN202411300626.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to efficiently and conveniently prepare pure phase, microporous high-entropy perovskite oxide materials, and the traditional sol-gel process is complex and inefficient.
Using acrylamide monomer copolymerization system with stronger binding force, the hydrogel is obtained through water bath heating, the moisture is removed, and the precursor powder is ground to obtain, and a high entropy perovskite oxide material is prepared by calcination, which is optimized for initiator and organics to shorten gel time.
It realizes efficient and convenient preparation of high-entropy perovskite oxide materials with small particle size, high purity and microporous, simplifies the process flow, reduces energy consumption, and improves the oxygen reduction catalytic activity of the material. It is suitable for SOFC and hydrogen and oxygen sensor.
Smart Images

Figure CN119191370A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic non-metallic material preparation, and relates to a high-entropy perovskite oxide material, and specifically to a preparation method of the high-entropy perovskite oxide material and its application in solid oxide fuel cells and hydrogen and oxygen sensors. Background Art
[0002] Solid oxide fuel cell (SOFC) is a new type of all-solid-state power generation device that can efficiently and environmentally convert chemical energy into electrical energy under medium and high temperature environments. It has broad application prospects in large or small distributed power stations, portable mobile energy, aerospace, national defense and other fields. In SOFC, the cathode is one of its core components, and the activation loss of the cathode is an important cause of its polarization loss. Therefore, it is crucial to prepare cathode materials with excellent performance for SOFC.
[0003] Oxygen sensors are generally used to detect the oxygen concentration in automobile exhaust gas, and play an important role in the exhaust emission system of automobiles. The oxygen concentration in the exhaust gas is detected by the oxygen sensor and fed back to the central control system, so that the fuel and oxygen in the automobile fuel chamber are fully burned, thereby reducing harmful gases in the exhaust gas. In addition, oxygen sensors have also been widely used in defense aviation, metallurgy, chemical industry, home appliances, medical treatment and other fields. The current sensitive electrode material of oxygen sensors is mainly platinum (Pt), which is a precious metal material and is expensive. Therefore, the development of sensitive electrode materials with excellent performance and low price is a research hotspot in the current development of oxygen sensors.
[0004] High-entropy perovskite oxide materials are composed of a variety of active metals, with synergistic effects and high-entropy effects. Their rich active sites, high catalytic activity and high stability make them widely used in the SOFC field. However, high-entropy perovskite oxide materials have a complex structure and various elements are evenly distributed, which poses a huge challenge to their preparation methods.
[0005] The solid phase method generally uses high-energy ball milling to prepare pure phase high-entropy perovskite oxide materials in large quantities, but it consumes a lot of energy, is easy to introduce impurities, and has uneven microscopic morphology. The chemical coprecipitation method adds a precipitant to a metal salt solution to obtain a composite oxide, which can obtain a nanopowder material with small particle size and uniform distribution, but the addition of a precipitant may cause agglomeration or uneven composition. Therefore, the efficient and convenient preparation of pure phase, microporous high-entropy perovskite oxide materials is a hot topic in the current field of research.
[0006] The traditional sol-gel method is to mix metal ions with organic and inorganic compounds. Due to the complexation, the solution is dried to form a gel, and then heat-treated to form an oxide. Although the high-entropy perovskite oxide material prepared in this way has a small particle size, is evenly mixed, is easy to dope with elements, and has a low reaction temperature and is easy to carry out, the traditional sol-gel method is not only complicated, but also takes a long time to prepare the gel, which greatly affects the efficiency. Summary of the invention
[0007] In view of this, the present invention discloses a high-entropy perovskite oxide material and a preparation method and application thereof, and specifically provides a new high-entropy perovskite oxide material preparation method. The preparation of high-entropy perovskite oxide material powder using this method is more efficient and convenient, and the prepared powder has high purity, small particle size, and microscopic pores.
[0008] It should be noted that the present invention adopts acrylamide monomer copolymerization system with stronger binding force, and the strong covalent bond directly solidifies the solution without long water drying, which greatly shortens the gel time. And through the optimization of initiator type and organic matter ratio, pure phase, small particle size, microscopic porous high entropy perovskite oxide material can be prepared efficiently and conveniently.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] The first technical purpose of the present invention is to provide a high entropy perovskite oxide material, wherein the molecular formula of the high entropy perovskite oxide material is AB x B y B z B η B θ O3 or A x A y A z A η A θ BO3(x+y+z+η+θ=1).
[0011] Specific chemical formula: BaCo 0.3 Fe 0.4 Zr 0.1 Y 0.1 Ni 0.1 O 3-δ (δ represents oxygen deficiency, which is determined by the material and is generally between 0 and 0.5).
[0012] A second object of the present invention is to provide a method for preparing the high entropy perovskite oxide material as described above, the method specifically comprising the following steps:
[0013] A) dissolving a soluble metal salt into deionized water, adding a monomer, a crosslinking agent, an initiator and an organic solvent, and stirring to obtain a mixture solution;
[0014] B) heating the mixture solution in a water bath to obtain a hydrogel after reaction;
[0015] C) crushing the gel and removing water to obtain a dry gel;
[0016] D) grinding the dry gel to obtain a precursor powder;
[0017] E) calcining the precursor powder to obtain a high entropy perovskite oxide material.
[0018] Optionally, the soluble metal salt is a nitrate or an acetate, and the soluble metal salt includes at least one of lanthanum nitrate, barium nitrate, cobalt nitrate, iron nitrate, zirconium nitrate, yttrium nitrate, nickel nitrate, manganese acetate, chromium acetate, and strontium nitrate, or a combination of any two or more thereof;
[0019] The monomer is one of acrylamide, acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate, or a combination of any two or more thereof;
[0020] The cross-linking agent is N,N-methylenebisacrylamide;
[0021] The initiator is at least one of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, and azobisisobutylamidine hydrochloride;
[0022] The organic solvent is one of anhydrous ethanol, methanol, ethylene glycol, propylene glycol, isopropanol, n-butanol, isobutanol, n-pentanol, and isopentanol, or a combination of any two or more thereof.
[0023] Furthermore, when the metal salt does not contain Fe and Cu metal salts, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide is 5:40:4, 0.05 g of azobisisobutyronitrile and 10 mL of anhydrous ethanol.
[0024] Furthermore, when the metal salt contains a metal salt of Fe or Cu, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide is 1:32:2, and then azobisisobutyronitrile is added in an amount equal to the total amount of the metal salt of Fe or Cu, and an appropriate amount of anhydrous ethanol is added to dissolve azobisisobutyronitrile according to its solubility in anhydrous ethanol.
[0025] Optionally, the reaction temperature of the water bath heating is 65-100° C., and the reaction time is 0.5-2 h.
[0026] Optionally, the method for removing moisture includes drying or freeze-drying; when drying is used to remove moisture, the drying temperature is 80-250° C. and the drying time is more than 5 hours.
[0027] Optionally, when grinding the dry gel, a ball milling method is used, with a ball milling speed of 400 to 870 r / min and a time of more than 20 min.
[0028] Optionally, the temperature and time of calcining the precursor powder are determined by the prepared material; specifically, the temperature of calcining the precursor powder is 600-1400° C., the time is 0.5-10 h, and the heating rate is 0.5-5° C. / min.
[0029] The third technical purpose of the present invention is to provide a high entropy perovskite oxide material prepared by the method as described above for use in solid oxide fuel cells and hydrogen and oxygen sensors.
[0030] Specifically, the high entropy perovskite oxide material prepared by the above method is used in SOFC cathode and oxygen sensor sensitive electrode.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The preparation method disclosed in the present invention is simple and convenient to operate, has low process energy consumption, and the prepared high-entropy perovskite oxide material has small particle size, high purity, good microscopic morphology, and good oxygen reduction catalytic activity. The present invention greatly improves the efficiency of material preparation, can be widely used in solid oxide fuel cell (SOFC) cathodes and hydrogen and oxygen sensor sensitive electrodes, and is an excellent preparation method for high-entropy perovskite oxide materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0034] Figure 1 The La prepared in Example 3 was used. 0.8 Sr 0.2 MnO 3-δ Graph of the sensing performance of the cathode material sensor to O2.
[0035] Figure 2The La prepared in Example 1 was used. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ Polarization impedance spectrum of a symmetric cell with cathode materials.
[0036] Figure 3 The La prepared in Example 1 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ XRD patterns of cathode materials.
[0037] Figure 4 The La prepared in Example 1 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ SEM image of cathode material.
[0038] Figure 5 The La prepared in Example 2 0.6 Sr 0.4 CoO 3-δ XRD patterns of cathode materials.
[0039] Figure 6 The La prepared in Example 3 0.8 Sr 0.2 MnO 3-δ XRD patterns of cathode materials.
[0040] Figure 7 The BaCo prepared in Example 4 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ Cathode material and BaCo prepared in Example 5 0.3 Fe 0.4 Zr 0.1 Y 0.1 Ni 0.1 O 3-δ XRD patterns of cathode materials.
[0041] Figure 8 The La prepared in Example 6 0.7 Sr 0.3 Co 0.2 Fe 0.2 Cr 0.2 Mn 0.2 Ni 0.2 O 3-δXRD patterns of cathode materials. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0044] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0045] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0046] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0047] The present invention discloses a method for preparing a high entropy perovskite oxide material, and the SOFC cathode material and manufacturing method involved can be used as a reference for ordinary technicians in the field, and the manufacturing process can be appropriately adjusted. In particular, it should be noted that for technicians in the field, all similar substitutions and modifications are within the scope of protection of the present invention. The present invention has described the methods and applications of the present invention through preferred embodiments, and relevant technicians can appropriately modify the methods and applications herein, or appropriately combine them without departing from the content, spirit and scope of the present invention.
[0048] The present invention provides a method for preparing a high-entropy perovskite oxide material. The high-entropy perovskite oxide material prepared by the present invention has abundant active sites, high catalytic activity and high stability, and is widely used in the SOFC field. The preparation method disclosed by the present invention is simple and convenient to operate, and the process energy consumption is low. The prepared high-entropy perovskite oxide material has small particle size, high purity and good microscopic morphology, which greatly improves the efficiency of material preparation.
[0049] The present invention provides a method for preparing a high entropy perovskite oxide material, comprising the following steps:
[0050] A) dissolving a metal salt in deionized water, adding acrylamide, N,N-methylenebisacrylamide, azobisisobutyronitrile and anhydrous ethanol, and stirring to obtain a mixture solution;
[0051] B) heating the mixture solution in a water bath to obtain a hydrogel after reaction;
[0052] C) crushing the gel and removing water to obtain a dry gel;
[0053] D) grinding the dry gel to obtain a precursor powder;
[0054] E) calcining the precursor powder to obtain a high entropy perovskite oxide material.
[0055] The method for preparing the high entropy perovskite oxide material provided by the present invention comprises firstly dissolving a soluble metal salt in deionized water, preferably using nitrate and acetate.
[0056] When the metal salt of the present invention does not contain Fe and Cu metal salt, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide includes but is not limited to 5:40:4, 0.05 g of azobisisobutyronitrile and 10 mL of anhydrous ethanol.
[0057] When the metal salt of the present invention contains a metal salt of Fe or Cu, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide includes but is not limited to 1:32:2, and then azobisisobutyronitrile is added in an amount equal to the total amount of the metal salt of Fe or Cu, and an appropriate amount of anhydrous ethanol is added to dissolve the azobisisobutyronitrile according to its solubility in anhydrous ethanol.
[0058] The stirring of the present invention is uniform to obtain a mixture solution; preferably, a magnetic stirrer is used for stirring; and the stirring reaction time is preferably 1.5 to 2 hours.
[0059] The water bath heating of the present invention is preferably specifically as follows: placing the beaker in a water bath at 85° C. and continuously stirring until a gel is formed.
[0060] The method of breaking the gel in the present invention preferably comprises breaking the whole gel into small pieces using a glass rod.
[0061] The dehydration step of the present invention is preferably as follows: placing the gel broken into small pieces in an oven at 150° C. to remove the moisture and form a dry gel.
[0062] The grinding of the xerogel in the present invention is preferably carried out by grinding the xerogel into precursor powder using an agate ball mill at a ball milling speed of 800 r / min.
[0063] The calcination of the precursor powder of the present invention is preferably as follows: the precursor powder is placed in a corundum crucible, placed in a muffle furnace, heated from room temperature to 1000° C. at 3° C. / min, calcined for 5 hours, and then naturally cooled to room temperature.
[0064] The present invention provides a method for preparing a high-entropy perovskite oxide material. The preparation method of the present invention is simple and convenient to operate, has low process energy consumption, and the prepared high-entropy perovskite oxide material has small particle size, high purity, good microscopic morphology, and good oxygen reduction catalytic activity. The present invention greatly improves the efficiency of material preparation, can be widely used in SOFC cathodes and hydrogen and oxygen sensor sensitive electrodes, and is an excellent method for preparing high-entropy perovskite oxide materials.
[0065] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0066] Example 1: La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ Powder preparation
[0067] Weigh 0.97476 g of La(NO3)3·xH2O (analytical grade), 0.42326 g of Sr(NO3)2 (analytical grade), 0.29107 g of Co(NO3)2·6H2O (analytical grade), and 1.61599 g of Fe(NO3)3·9H2O (analytical grade) and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical grade), 2.4668 g of N,N-methylenebisacrylamide (97%), 0.65 g of azobisisobutyronitrile (98%), and 50 g of anhydrous ethanol. mL to obtain a mixed solution; stir the mixed solution with a magnetic stirrer for two hours; put the solution into a water bath and heat it at 85°C with a stirring speed of 300r / min until the aqueous solution becomes a gel; crush the gel with a glass rod and put it into a 150°C oven for drying for 5 hours to remove moisture to obtain a dry gel; use an agate ball mill to ball grind the dry gel into a precursor powder at a ball mill speed of 800r / min; put the precursor powder into a corundum crucible and calcine it at 1000°C in a muffle furnace for 5 hours to obtain the SOFC cathode material - La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ Powder material.
[0068] Example 2: La 0.6 Sr 0.4 CoO 3-δ Powder preparation
[0069] Weigh 0.97476 g of La(NO3)3·xH2O (analytical grade), 0.42326 g of Sr(NO3)2 (analytical grade), and 1.45535 g of Co(NO3)2·6H2O (analytical grade) and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical grade), 2.4668 g of N,N-methylenebisacrylamide (97%), 0.02 g of azobisisobutyronitrile (98%), and 5 mL of anhydrous ethanol to obtain a mixed solution. The liquid was stirred with a magnetic stirrer for two hours; the solution was placed in a water bath and heated at 85°C with a stirring speed of 300r / min until the aqueous solution became a gel; the gel was crushed with a glass rod and placed in a 150°C oven for drying for 5 hours to remove moisture to obtain a dry gel; the dry gel was ball-milled into a precursor powder using an agate ball mill at a ball mill speed of 800r / min; the precursor powder was placed in a corundum crucible and calcined at 800°C in a muffle furnace for 5 hours to obtain the SOFC cathode material - La 0.6 Sr 0.4 CoO 3-δ Powder material.
[0070] Example 3: La 0.8 Sr 0.2MnO 3-δ Powder preparation
[0071] Weigh 1.29968 g of La(NO3)3·xH2O (analytical grade), 0.21163 g of Sr(NO3)2 (analytical grade), and 0.86515 g of C4H6MnO4 (98%) and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical grade), 2.4668 g of N,N-methylenebisacrylamide (97%), 0.02 g of azobisisobutyronitrile (98%), and 5 mL of anhydrous ethanol to obtain a mixed solution. The mixture was stirred for two hours with a force stirrer; the solution was placed in a water bath and heated at 85°C with a stirring speed of 300 r / min until the aqueous solution became a gel; the gel was crushed with a glass rod and placed in a 150°C oven for drying for 5 hours to remove moisture to obtain a dry gel; the dry gel was ball-milled into a precursor powder using an agate ball mill at a ball mill speed of 800 r / min; the precursor powder was placed in a corundum crucible and calcined at 900°C in a muffle furnace for 5 hours to obtain the SOFC cathode material, La 0.8 Sr 0.2 MnO 3-δ Powder material.
[0072] Example 4: BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ Powder preparation
[0073] Weigh 1.3067 g of Ba(NO3)2 (chemically pure), 0.5821 g of Co(NO3)2·6H2O (analytical pure), 0.808 g of Fe(NO3)3·9H2O (analytical pure), 0.21466 g of Zr(NO3)4·5H2O (analytical pure), and 0.1915 g of Y(NO3)3·6H2O (99.99%) and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical pure), 2.4668 g of N,N-methylenebisacrylamide (97%), and 0. 35g of sodium methacrylate and 30mL of anhydrous ethanol were added to obtain a mixed solution; the mixed solution was stirred for two hours with a magnetic stirrer; the solution was placed in a water bath and heated at 85°C and a stirring speed of 300r / min until the aqueous solution became a gel; the gel was crushed with a glass rod and placed in a 150°C oven for drying for 5h to remove moisture to obtain a dry gel; the dry gel was ball-milled into a precursor powder using an agate ball mill at a ball mill speed of 800r / min; the precursor powder was placed in a corundum crucible and calcined at 1000°C in a muffle furnace for 5h to obtain the SOFC cathode material, namely BaCo 0.4 Fe 0.4 Zr0.1 Y 0.1 O 3-δ Powder material.
[0074] Example 5: BaCo 0.3 Fe 0.4 Zr 0.1 Y 0.1 Ni 0.1 O 3-δ Powder preparation
[0075] Weigh 1.3067g of Ba(NO3)2 (chemically pure), 0.4366g of Co(NO3)2·6H2O (analytical pure), 0.808g of Fe(NO3)3·9H2O (analytical pure), 0.21466g of Zr(NO3)4·5H2O (analytical pure), 0.1915g of Y(NO3)3·6H2O (99.99%), and 0.1454g of Ni(NO3)2·6H2O (98%) and dissolve them in 100mL of deionized water. Then add 17.06g of acrylamide (analytical pure), 2.4668g of N,N-methylenebisacrylamide (97%), 0.35 g of azobisisobutyronitrile (98%) and 30 mL of anhydrous ethanol were added to obtain a mixed solution; the mixed solution was stirred with a magnetic stirrer for two hours; the solution was placed in a water bath and heated at 85°C and a stirring speed of 300 r / min until the aqueous solution became a gel; the gel was crushed with a glass rod and placed in a 150°C oven for drying for 5 hours to remove moisture to obtain a dry gel; the dry gel was ball-milled into a precursor powder using an agate ball mill at a ball mill speed of 800 r / min; the precursor powder was placed in a corundum crucible and calcined at 1000°C in a muffle furnace for 5 hours to obtain the SOFC cathode material, BaCo 0.3 Fe 0.4 Zr 0.1 Y 0.1 Ni 0.1 O 3-δ Powder material.
[0076] Example 6: La 0.7 Sr 0.3 Co 0.2 Fe 0.2 Cr 0.2 Mn 0.2 Ni 0.2 O 3-δ Powder preparation
[0077] Weigh 0.56861 g of La(NO3)3·xH2O (analytical grade), 0.15872 g of Sr(NO3)2 (analytical grade), 0.14553 g of Co(NO3)2·6H2O (analytical grade), 0.202 g of Fe(NO3)3·9H2O (analytical grade), 0.11457 g of C6H9O6Cr (99.9%), 0.0865 g of C4H6MnO4 (98%), and 0.1454 g of Ni(NO3)2·6H2O (98%) and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical grade), 17.06 g of N,N-methylenebisacrylamide (9 7%) 2.4668g, azobisisobutyronitrile (98%) 0.1g and anhydrous ethanol 15mL to obtain a mixed solution; the mixed solution was stirred with a magnetic stirrer for two hours; the solution was placed in a water bath and heated at 85°C and a stirring speed of 300r / min until the aqueous solution became a gel; the gel was crushed with a glass rod and placed in a 150°C oven for drying for 5h to remove moisture to obtain a dry gel; the dry gel was ball-milled into a precursor powder using an agate ball mill at a ball mill speed of 800r / min; the precursor powder was placed in a corundum crucible and calcined at 1000°C in a muffle furnace for 5h to obtain the SOFC cathode material - La 0.7 Sr 0.3 Co 0.2 Fe 0.2 Cr 0.2 Mn 0.2 Ni 0.2 O 3-δ Powder material.
[0078] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples and test examples are used to further illustrate the technical features of the preparation method and application disclosed in the present invention, but they should not be understood as limitations of the present invention. Other improvements made by those skilled in the art based on the above invention content without creative work are also considered to fall within the scope of protection of the present invention.
[0079] Comparative Example 1: La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ Powder preparation
[0080] Weigh 0.97476 g of La(NO3)3·xH2O (analytical grade), 0.42326 g of Sr(NO3)2 (analytical grade), 0.29107 g of Co(NO3)2·6H2O (analytical grade), and 1.61599 g of Fe(NO3)3·9H2O (analytical grade), and dissolve them in 100 mL of deionized water. Then add 17.06 g of acrylamide (analytical grade), 2.4668 g of N,N-methylenebisacrylamide (97%), 0.02 g of azobisisobutyronitrile (98%), and 15 mL of anhydrous ethanol to obtain a mixed solution. Stir the mixed solution with a magnetic stirrer for two hours. Heat the solution in a water bath at 85°C and a stirring speed of 300 r / min. No gel is formed after 10 hours.
[0081] Contains Fe 3+ , Cu 2+ Strong oxidizing metal ions such as 2-(4-(2-nitrogen)-2-nitrogen) and 2-(4-nitrogen)-2-nitrogen will react with the free radicals generated by the initiator, resulting in the termination of the polymerization reaction. Therefore, we optimized the ratio of the initiator and achieved rapid gelation according to the preparation method of Example 1.
[0082] like Figure 3 , 5 As shown in Figures 6, 7, and 8, all of our embodiments are highly consistent with the standard XRD patterns, and pure oxide powders are obtained without any impurities. Figure 4 As shown, the oxide powder prepared by the present invention has a small and uniform particle size and an overall microscopic porous structure, which is very suitable for gas catalytic reactions. Figure 2 As shown, the symmetrical cell prepared based on the gadolinium-doped cerium oxide electrolyte sheet using the LSCF cathode material prepared in Example 1 measured a relatively small polarization impedance, indicating that the cathode material has excellent ORR catalytic performance, which is inseparable from its good microscopic morphology. Figure 1 As shown, the sensor prepared based on the yttrium-stabilized zirconia electrolyte sheet using the LSM cathode material prepared in Example 3 has excellent sensing performance for O2, with fast response speed, high resolution and continuous stability.
[0083] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high entropy perovskite oxide material, characterized in that: The molecular formula of the high entropy perovskite oxide material is AB x B y B z B η B θ O3 or A x A y A z A η A θ BO3(x+y+z+η+θ=1).
2. A method for preparing a high entropy perovskite oxide material as claimed in claim 1, characterized in that: The method specifically comprises the following steps: A) dissolving a soluble metal salt into deionized water, adding a monomer, a crosslinking agent, an initiator and an organic solvent, and stirring to obtain a mixture solution; B) heating the mixture solution in a water bath to obtain a hydrogel after reaction; C) crushing the gel and removing water to obtain a dry gel; D) grinding the dry gel to obtain a precursor powder; E) calcining the precursor powder to obtain a high entropy perovskite oxide material.
3. The method for preparing a high entropy perovskite oxide material according to claim 2, characterized in that: The soluble metal salt is a nitrate or an acetate, and the soluble metal salt includes at least one of lanthanum nitrate, barium nitrate, cobalt nitrate, iron nitrate, zirconium nitrate, yttrium nitrate, nickel nitrate, manganese acetate, chromium acetate, and strontium nitrate, or a combination of any two or more thereof; The monomer is one of acrylamide, acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate, or a combination of any two or more thereof; The cross-linking agent is N,N-methylenebisacrylamide; The initiator is at least one of azobisisobutyronitrile, ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, and azobisisobutylamidine hydrochloride; The organic solvent is one of anhydrous ethanol, methanol, ethylene glycol, propylene glycol, isopropanol, n-butanol, isobutanol, n-pentanol, and isopentanol, or a combination of any two or more thereof.
4. The method for preparing a high entropy perovskite oxide material according to claim 3, characterized in that: When the metal salt does not contain Fe and Cu metal salt, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide is 5:40:4, 0.05 g of azobisisobutyronitrile and 10 mL of anhydrous ethanol.
5. The method for preparing a high entropy perovskite oxide material according to claim 3, characterized in that: When the metal salt contains a metal salt of Fe or Cu, the ratio of the total amount of metal ions in the metal salt to acrylamide and N,N-methylenebisacrylamide is 1:32:2, and then azobisisobutyronitrile is added in an amount equal to the total amount of the metal salt of Fe or Cu, and an appropriate amount of anhydrous ethanol is added to dissolve the azobisisobutyronitrile according to its solubility in anhydrous ethanol.
6. The method for preparing a high entropy perovskite oxide material according to claim 2, characterized in that: The reaction temperature of the water bath heating is 65-100° C., and the reaction time is 0.5-2 h.
7. The method for preparing a high entropy perovskite oxide material according to claim 2, characterized in that: The method for removing moisture includes drying or freeze-drying; when drying is used to remove moisture, the drying temperature is 80-250° C. and the drying time is more than 5 hours.
8. The method for preparing a high entropy perovskite oxide material according to claim 2, characterized in that: When grinding the dry gel, a ball milling method is used, with a ball milling speed of 400 to 870 r / min and a time of more than 20 minutes.
9. The method for preparing a high entropy perovskite oxide material according to claim 2, characterized in that: The temperature of the calcined precursor powder is 600-1400° C., the time is 0.5-10 hours, and the heating rate is 0.5-5° C. / min.
10. Use of the high entropy perovskite oxide material as claimed in claim 1 or the high entropy perovskite oxide material prepared by the method as claimed in claim 2 in solid oxide fuel cells and hydrogen and oxygen sensors.
Citation Information
Cited By
High-entropy perovskite cathode material and preparation method and application thereof
CN120473515A
